Literature Review of the Five Elements of Speech Community - Sirisrisudakul , Pimwarin (Journal of Sinology (วารสารจีนวิทยา), 2013)
Currently, there is a much debate about which elements must be considered in forming the Speech Community. Through summarizing and analyzing, there are five elements that should be considered in forming the Speech Community, including "region", "population", "facilities", "interaction" and "identity". Each element is equally important, so they must have a close relationship and must act together. If any element misses from the feature or does not meet the standard conditions, it won’t be able to form a Speech Community.